Al-Yahūd fī mu’allafāt al-muslimīn bi Indonesia: Dirāsah awwalīyah - Ropi, Ismatu (Studia Islamika, 2019)
This article tries to map out more than 40 works of Indonesian Muslim writers regarding the Jews (as religion and communities), and the influences of those works in shaping understanding on Judaism and the Jews among Indonesian Muslim communities. This article focuses on examining how those writers interested to the themes they choose in their books, and what are the sources they refer to. In general, there are at least two models of Indonesian Muslim writers have developed in their works on Judaism and the Jews community. The first is the works that are normatively preferring to based their primary sources from the Quran and al-Hadith or classical Muslim scholarship traditions in their depiction on Judaism or the Jews. The second is the works that are mainly characterized to prove Jewish ‘hidden’ agendas as well as political, social, economic and cultural movements played by the Jews as a part of international Jewish connection.